Energy Sources of the Depth-Generalist Mixotrophic Coral Stylophora pistillata - Stephane Martinez; Stephane Martinez; Yuval Kolodny; Yuval Kolodny; Eli Shemesh; Federica Scucchia; Federica Scucchia; Reinat Nevo; Smadar Levin-Zaidman; Yossi Paltiel; Yossi Paltiel; Nir Keren; et al. (Frontiers in Marine Science, 2020)
Energy sources of corals, ultimately sunlight and plankton availability, change dramatically from shallow to mesophotic (30–150 m) reefs. Depth-generalist corals, those that occupy both of these two distinct ecosystems, are adapted to cope with such extremely diverse conditions. In this study, we investigated the trophic strategy of the depth-generalist hermatypic coral Stylophora pistillata and the ability of mesophotic colonies to adapt to shallow reefs. We compared symbiont genera composition, photosynthetic traits and the holobiont trophic position and carbon sources, calculated from amino acids compound-specific stable isotope analysis (AA-CSIA), of shallow, mesophotic and translocated corals. This species harbors different Symbiodiniaceae genera at the two depths: Cladocopium goreaui (dominant in mesophotic colonies) and Symbiodinium microadriaticum (dominant in shallow colonies) with a limited change after transplantation. This allowed us to determine which traits stem from hosting different symbiont species compositions across the depth gradient. Calculation of holobiont trophic position based on amino acid δ15N revealed that heterotrophy represents the same portion of the total energy budget in both depths, in contrast to the dogma that predation is higher in corals growing in low light conditions. Photosynthesis is the major carbon source to corals growing at both depths, but the photosynthetic rate is higher in the shallow reef corals, implicating both higher energy consumption and higher predation rate in the shallow habitat. In the corals transplanted from deep to shallow reef, we observed extensive photo-acclimation by the Symbiodiniaceae cells, including substantial cellular morphological modifications, increased cellular chlorophyll a, lower antennae to photosystems ratios and carbon signature similar to the local shallow colonies. In contrast, non-photochemical quenching remains low and does not increase to cope with the high light regime of the shallow reef. Furthermore, host acclimation is much slower in these deep-to-shallow transplanted corals as evident from the lower trophic position and tissue density compared to the shallow-water corals, even after long-term transplantation (18 months). Our results suggest that while mesophotic reefs could serve as a potential refuge for shallow corals, the transition is complex, as even after a year and a half the acclimation is only partial.